Variety Show with Indonesian Culture among the Imperialism of Foreign Culture - Noor, Ady Ferdian; Sari, Erika; Nurbudiyani, Iin; Fatchurahman, M.; Haryadi, Haryadi; Herman, Herman; Ningsih, Irma; Oktariana, Devita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Variety show infotainment program that was successful in society and became a topic of conversation in public communication. Indonesian society in 11 cities was seen 90% happy to watch television in 2017. The program was full of gossip about the lives of artists at that time. The show gave birth to changes in ethical values that could damage the cultural order of the Indonesian nation as an eastern society that upholds good manners. Aim: The purpose of the study was to determine whether cultural values, religion, and social norms in Indonesian society are the main elements in every variety show broadcast on television. Method: The research method used a type of literature review with a qualitative descriptive approach through analysis of reports, articles, and library books, then analyzed descriptively inductively to produce conclusions. Result and Discussions: The results of the study, the government implemented the broadcasting law as a form of multicultural communication policy to control foreign cultural imperialism. Conclusion: The government implemented the protection of Indonesian culture through the broadcasting law and encouraged the emergence of multicultural values on Indonesian television.